High YAP and TEAD4 immunolabelings are associated with poor prognosis in patients with gallbladder cancer. Issue 12 (14th November 2021) - Kim, Joo Young; Sung, You‐Na; Hong, Seung‐Mo
Abstract : Yes‐associated protein (YAP) and TEA domain‐containing sequence‐specific transcription factors 4 (TEAD4) are essential components of the Hippo pathway. Abnormal regulation of the Hippo pathway contributes to the progression and metastasis of many cancer types. However, their clinicopathologic and prognostic significances have not been studied in gallbladder cancers. Here, we systematically evaluated the YAP and TEAD4 immunolabelings and their association with clinicopathologic characteristics and survival outcomes using 212 specimens of surgically resected gallbladder cancers. High YAP and TEAD4 immunolabelings were identified in 70 (33%) cases and were associated with infiltrative growth pattern, poor differentiation, perineural invasion, and advanced pT classification and AJCC stage. High YAP immunolabeling was significantly associated with high TEAD4 immunolabeling (p < 0.001). High immunolabeling levels of YAP or TEAD4 alone and the combined YAP high TEAD4 high group were significantly associated with poor survival in both univariate (p < 0.001) and multivariate analyses (HR = 2.358; 95% CI, 1.369–4.061; p = 0.002). Therefore, the YAP and TEAD4 immunolabelings are associated with aggressive behavior of gallbladder cancers and may be useful as a prognostic indicator in patients with surgically resected gallbladder cancer.